KAJIAN SENI KRIYA MELALUI PENDEKATAN SEMIOTIK ROLAND BARTHES - Mr. Andono (Ars: Jurnal Seni Rupa dan Desain, 2007)
work o f art .is. in essence, a language in its visual form. It is the visualisation o f the jtersonalexpression o f an artist. Nowadays, a work o f art not merely possesses a practical function but also becomcsan expressive work in a two or three-dimensional format. Therefore, it can be considered as a text containingcertain meanings and messages which can be analysed, for example, using a semiotics approach. Thisanalysis can be carried out since there is a seiniotic proccss involving the signs within a work o f art.Roland Barthes presents a theory o f mythical analysis in his semiotics approach which is called"the order seiniological system. " It consists o f two levels, i.e. language as the first order semiological system,and myth as the second. The first level is a denotation level. A work o f art - as an image - possesses an iconicmessage. An explanation at this level gives meaning to the literal or the non-coded iconic message whichcan be seen from indicators o f observable reality. The second level (level o f connotation) is the reading o f thesymbolic message, -which is based on a certain cultural code or familiarity towards a particular stereotype.In this case, an image or artwork with such a connotation signifies an ideology, while that being signifiedis called rhetoric or cannot at or.Works to be analysed are /DM. Mekomatia's “Dikejar Waktu" and Uliana Iraw.vii's "Tak AdaBatas." These are examples o f images which possess iconic messages: literal/denotative as well as symbolic.In addition, they also contain a contextual "text" (the title o f the work). The structure is able to be usedas a reference in giving meaning or reading a urork o f art, denotatively and connotatively as well. Tnecommunicative relationship behoeen the existing iconic messages guides a person in giving it meaning.Keywords: art, semiotics, mythical theory